Penerapan Model ASSURE dengan Menggunakan Media Quizwhizzer dalam Pembelajaran Menganalisis Sistematika dan Kebahasaan Karya Ilmiah Kelas XI - Fitri Andriani; Dina Luluk Kamalia; Muhammad Ridho; Lilik Hariyanti; Aji Utomo; Asep Purwo Yudi Utomo; Diyamon Prasandha (CV. Aksara Global, 2023)
The skills to analyze systematics and language of scientific work are very important for students to master. However, based on observations, several Indonesian language teachers at SMAN 4 Semarang still apply teacher-dominated learning, namely lectures and power points as learning media which make learning not student centered so that when participating in learning the students feel bored. Therefore, the ASSURE model was tested using Quizwhizzer media in learning to analyze the systematics and language of scientific work in class XI.MIPA3 SMAN 4 Semarang with the aim of creating student-centered learning, increasing student interest in learning and activeness, and optimizing student learning outcomes. This research method is descriptive qualitative with test and non-test instruments (questionnaire). Test instruments are used with test techniques as material for analyzing the effectiveness of the learning process. While the non-test technique is used with observation and questionnaire techniques as material for analyzing the characteristics of students and assessing the effectiveness of the learning process. The results of this study can be concluded that the ASSURE model with Quizwhizzer media is appropriately applied in learning to analyze the systematics and language of scientific work. The results of this study are useful as reference material in choosing learning models and media, especially learning models and media to analyze the systematics and language of scientific work.